Pewarisan Nilai Budaya Religius Dalam Membentuk Kesalihan Sosial Anak Dan Generasi Muda - Kasidi Kasidi; Supiah Supiah; Mariaty Podungge (Universitas Muhammadiyah Makassar, 2023)
The flow of information and the rapid development of social media with various kinds of audio-visual presentations, both positive and negative at the same time, of course raises anxiety about the impact it has on human behavior, especially for children and the younger generation. Apart from that, there are many factors of social destructiveness and promiscuity which are very easy to access, of course, it also has an impact on the more difficult efforts to form piety in social life for them. This study aims to determine the importance of inheriting religious cultural values in shaping the social piety of children and the younger generation. This type of research is literature study, the method used is a qualitative method with a description that takes into account relevant and value-oriented contexts, this research is descriptive in nature which focuses on systematic explanations and context analysis. The results of the study show that parents have a responsibility to shape social piety for children and the younger generation by being role models for them in living real life in the midst of worldly associations that challenge and threaten the character of children and the nation's generation, because of this the inheritance of cultural values. This religus for them is very urgent and must be sustainable by enriching narratives and deepening scientific and religious insights without neglecting the development of digital technology under the supervision of educators, especially parents.Keywords: Inheritance, Values, Culture, religious, Charity, social.